2019
DOI: 10.1590/fst.11218
|View full text |Cite
|
Sign up to set email alerts
|

Equine milk and its potential use in the human diet

Abstract: Dur objective was to address the use of equine milk for human consumption, highlighting important compositional aspects and peculiar characteristics of this milk. Equine milk stands out for its similarity to breastmilk in compositional aspects considering the quality of the protein and lipid fractions, and due to the presence of important bioactive compounds. The high percentage of whey proteins and the structure of the protein micelles favor equine milk's digestibility, while its bioactive protein richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…The reason for such significant differences is due to variations between inter alia, casein, and fat contents. Mare's milk contains 21.4% protein (50% casein, 38.8% whey protein) [26]. The casein content in mare's milk is lower than in cow's milk and is the reason why mare's milk is included in so-called albumin milks [23].…”
Section: Color Of Mare's and Other Milksmentioning
confidence: 99%
“…The reason for such significant differences is due to variations between inter alia, casein, and fat contents. Mare's milk contains 21.4% protein (50% casein, 38.8% whey protein) [26]. The casein content in mare's milk is lower than in cow's milk and is the reason why mare's milk is included in so-called albumin milks [23].…”
Section: Color Of Mare's and Other Milksmentioning
confidence: 99%
“…In a clinical study it has been found that 60 days koumiss consumption by patients alleviated the signs of chronic atrophic gastritis as verified with a reduction in blood cholesterol and platelet levels via modulating gut microbiota (Li et al 2017). Koumiss is an utmost digestible food due to the presence of high percentage of whey protein: casein ratio as well as presence of spongiform structure of protein that enhance digestibility and its consumption has beneficial effects in treating atopic dermatitis, and chronic diseases of GIT (Barreto et al 2019). Thus koumiss have shown positive effects on the kidneys, liver, endocrine glands, blood formation organs, and the digestive, nervous, immune and cardiovascular systems in addition to healing effects on disorders such as anemia, a-vitaminosis, gastric and intestinal diseases (Sanlier et al 2019)…”
Section: Koumissmentioning
confidence: 99%
“…Studies on the benefits of bovine colostrum for humans have been developed for centuries, although they are still not yet fully elucidated (Bodammer et al, 2011). On addition, in a review of equine colostrum, Barreto et al (2019) also elucidated several benefits in food and human health. Therefore, the present review aims to address the use of bovine colostrum for human consumption, taking into account its nutritional composition and the presence of functional compounds such as enzymes and growth factors.…”
Section: Introductionmentioning
confidence: 99%